Legal Security of Public Administration in Ukraine during the Conditions of Martial State: Theoretical Aspects and Practice - Lakhyzha, Mykola; Kachan, Yana (Theory and Practice of Public Administration, 2022)
This article is the first and planned publication by the authors of the results of the study of legal, organizational and informational support for the effective functioning of public administration in Ukraine under martial law. In order to identify and generalize the characteristic features of the transformation of public administration under martial law, the authors analyzed normative legal acts, the results of sociological research, and materials from the websites of Ukrainian authorities. A thematic review of scientific publications was also conducted. The red thread in the article is the idea of the need to combine ensuring the adequacy of public administration to the conditions of martial law and preserving democracy with the aim of maximally realizing the rights and freedoms of citizens and their active participation in countering the enemy. It is argued that the legal provision of public administration in the conditions of martial law is based on a number of normative legal acts adopted before the beginning of the war. The tasks and directions of regulatory and legal support for the transformation of public administration are revealed.